Schools Have Contextual Influence on Smoking Behavior among High School Students in Dumai, Riau - Shilfia Ulfa Islami; Hanung Prasetya; Bhisma Murti (Journal of Health Promotion and Behavior, 2019)
Background: Adolescence is prone to smoking behavior. Smoking behavior in adolescents is influenced by parental income factors, pocket money, media exposure, peers, the influence of parents, and attitudes towards smoking behavior. The purpose of this study was to analyze the contextual influence of school on smoking behavior in adolescents in Dumai City, Riau.Subject and Method: This was a cross sectional study conducted at 13 senior high schools and 12 junior high schools in Dumai, Riau, Indoneisa, from September to October 2019. A sample of 200 male adolescents aged 12-18 years was selected by stratified random sampling. The dependent variable was smoking behavior. The independent variables were parental income, pocket money, media exposure, peer, parental influence, intention, attitude, subjective norm, and perceived behavior control (PBC). The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression run on Stata 13.Results: Smoking behavior in male adolescents increased with high parental income (b= 2.06; 95% CI= -0.02 to 4.15; p=0.053), high pocket money (b=2.75; 95% CI= 0.80 to 4.71; p= 0.006), high exposure to cigarette advertising media (b= 2.45; 95% CI= 0.52 to 4.37; p=0.012), peer (b=2.10; 95% CI= 0.46 to 3.74; p=0.012), parental smoking behavior (b= 2.23; 95% CI= 0.47 to 3.99; p=0.013), and positive attitude to smoke (b= 2.67; 95% CI= 0.78 to 4.55; p=0.005). Smoking behavior decreased with weak PBC (b= -2.33; 95% CI= -405 to -0.60; p= 0.008), weak intention (b= -3.85; 95% CI= -6.32 to -1.39; p= 0.002), and weak subjective norm (b=-3.03; 95 % CI= -5.16 to 5.16; p= 0.005). There was strong contextual effect of school on smoking behavior in male adolescents with intra-class (ICC)= 25.14%.Conclusions: Smoking behavior in male adolescents increases with high parental income, high pocket money, high exposure to cigarette advertising media, peer, parental smoking behavior, and positive attitude to smoke. Smoking behavior decreases with weak PBC, weak intention, and weak subjective norm. There is strong contextual effect of school on smoking behavior in male adolescents.Keywords: smoking behavior, adolescents, schoolCorrespondence: Shilfia Ulfa Islami. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: shilfiaulfa17@gmail.com. Mobile: 085219722029.Journal of Health Promotion and Behavior (2019), 4(3): 212-223https://doi.org/10.26911/thejhpb.2019.04.03.06